O-068 The BISTIM study: first RCT comparing dual ovarian stimulation on the same cycle (duostim) vs 2 conventional ovarian stimulations in poor ovarian responders undergoing IVF. (30th June 2022) - Massin, N; Chevalier, N; Descat, E; Piétin-Vialle, C; Bry-Gauillard, H; Issa, A; Brussieux, M; Pasquier, M; Porcu-Buisson, G
Abstract: Study question: Is the number of cumulated oocytes with dual ovarian stimulation on the same cycle (duostim) higher compared to 2 consecutive antagonist cycles in poor responders? Summary answer: Considering the number of total and mature oocytes collected in poor ovarian responders, there is no benefit of duostim vs two consecutive antagonist cycles. What is known already: Several waves of follicular development exist on the same cycle. Recent studies have shown the ability to obtain oocytes with equivalent quality in the luteal phase, even after a previous ovarian stimulation in the follicular phase. During stimulation, smaller follicles are recruited and sensitized, which may increase the selection of follicles available on the second stimulation. In poor ovarian responders (POR) this potentialization may have a great interest, as 2 stimulations on the same cycle could give a higher number of oocytes compared to two conventional stimulations. However, these preliminary data need to be confirmed with a randomized controlled trial. Study design, size, duration: This is a multicenter, open-labeled randomized control trial (2018, september – 2021, march). The primary objective was to demonstrate that two ovarian stimulations within the same cycle (first in the follicular phase, followed by a second in the luteal phase) lead to the retrevial of 1.5 more oocytes than the cumulative number of oocytes from two consecutive conventional stimulation, in POR women. According to this hypothesis, 44 patients were needed in each group. Participants/materials, setting, methods: 88 POR women, defined with Bologna criteria (AFC≤5 and/or AMH≤1.2ng/ml and ≤3 oocytes if previous IVF) were randomized, 44 in duostim group (D) and 44 in conventional group (C). FertistartKit® 300IU/day with antagonist protocol was used except in luteal phase stimulation of group D. In group D, oocytes were pooled and inseminated after the second retrieval, with freeze all embryos. Fresh transfer was performed in group C. The analysis is presented in intention to treat. Main results and the role of chance: There was no difference between the groups regarding demographics, ovarian reserve markers (AFC, AMH) and stimulation parameters. The mean number of cumulated oocytes retrieved with 2 ovarian stimulation was not statistically different in group D and C, respectively 5.0+/-3.4 and 4.6+/-3.4 (p = 0.56). The mean number of cumulated mature oocytes was not statistically different, 3.7+/-3.3 in group D vs 3.1+/-3.0 in group C (p = 0.38). The mean number of embryos was significantly lower in the group D, 0.8+/-1.3 vs group C 1.6+/-1.3 (p < 0.01). There was no statistical difference of the mean number of oocytes retrieved per cycle in cycle 1 vs cycle 2 in both group D and C. The delay, between the first and the second day 1 of stimulation was statistically different in group D 14.4 days (10-19) vs group C 90.6 (28-232). The ongoing pregnancy rate in group D 17.9% (7/39) was not statistically different with group C 29.3% (12/41), (p = 0.23). And the mean time to ongoing pregnancy tends to be longer in group D (144 days) vs group C (115 days) but was not statistically different (p = 0.21). Limitations, reasons for caution: The RCT was impacted by Covid pandemia and stop of IVF activities for 10 weeks. Delays were recalculated to exclude this period, however one women in group D cannot have the luteal stimulation. We also faced unexpected good ovarian responses and pregnancies after the first oocyte pick-up in group C. Wider implications of the findings: In routine practice, the benefit of duostim in patients with POR is not confirmed. Firstly, because there is no potentialization on the number of oocyte retrieved in luteal phase after follicular phase stimulation. Secondly, because the freeze all strategy avoids a pregnancy with fresh embryo transfer after the first cycle. Trial registration number: 2017-A00498-45